Relevansi Risalatu Al-Qada' Umar terhadap Etika Profesi Hakim di Indonesia - Dulsukmi Kasim (Al-Mizan (e-Journal), 2016)
Professional ethics of a judge is something that is universal, meaning adopted, recognized, and found in the country's legal system, anytime and anywhere. That's because the problem was related to the problem of moral values, kindness, and decency which ideally is indeed the behavior and moral values that should always be held firmly by a who is a judge in performing their duties. In fact, it is not enough merely preserved, moral values are also always dibugarkan and developed in carrying out their duties. Relation risalatul al-qada' is very relevant to the professional ethics of judges in Indonesia because it contains in it the principle of the independence of judges in performing their duties; equality and fairness by not distinguishing between litigants; the principles of professionalism and has a personality that is unimpeachable; and the normative theological principles and peace.